A new flavonoid from the leaves of Garcinia mckeaniana Craib and α-glucosidase and acetylcholinesterase inhibitory activities. Issue 19 (21st September 2022) - Nguyen, Thi Thu Ha; Nguyen, Van Tuyen; Van Cuong, Pham; Nguyen Thanh, Tra; Le Thi, Tu Anh; Mai Huong, Doan Thi; Truong, Bich Ngan; Litaudon, Marc; Ninh The, Son
Abstract: From the ethyl acetate extract (EtOAc) of the Vietnamese Garcinia mckeaniana leaves, a new flavone 8- C -glycoside 2'', 6''-di- O -acetylvitexin (1 ), together with six known analogs 2-7 were isolated. Their structures were determined by spectral methods and compared with literature data. In α-glucosidase inhibitory assay, the EtOAc extract and its flavone and biflavone derivatives possessed the significant IC50 range of 9.17-97.53 µM, as compared with that of the positive control acarbose (249 µM). Flavones and biflavones showed are better than flavone glycosides in both α-glucosidase and acetylcholinesterase inhibitory activities